Mothers, Fathers and Children after Divorce: The Role of Institutions - Daniela Del Boca (Institute for the Study of Labor (IZA), 2002)
In recent years the increase in the divorce rate in many advanced countries and the predominance of female-headed families among the poor has generated much interest in the relationship between divorce and the welfare of mothers and children. In this paper I will review a small body of economic literature which has been recently developed in order to analyze the economic consequence of divorce on the welfare of fathers, mothers and children under alternative behavioral assumptions. Important economic and econometric issues arise from an analysis of welfare in non intact households as compared with intact households. In particular the focus is on the role that institutions play in post-divorce arrangements and important implications concerning policies for child support, custody, and visitation.
Keywords: K40; D10; 330; Divorce; intra-household allocation; children welfare; Alleinerziehende; Haushaltsökonomik; Lebensstandard; Institutionalismus; Kinderbetreuung; Ehe; Wohlfahrtseffekt; Schätzung; Vereinigte Staaten